Indonesia Economic Quarterly, June 2009 : Weathering the Storm - World Bank (World Bank, Washington, DC, 2018)
Indonesia's slowdown has come relatively later and been more moderate than for many countries but the adverse effects of the global economic slowdown are now playing out. Gross Domestic Product (GDP) growth slowed in the fourth quarter of 2008 and into the first quarter of 2009, to 4.4 percent year-on-year, from 6.4 percent in the year to the third quarter. For 2008 as a whole the Indonesian economy expanded by 6.1 percent, only slightly below 2007's 6.3 percent pace. Nevertheless, all sectors of the economy were impacted during the period of peak turbulence in global financial markets in late 2008. Into the first quarter of 2009 externally focused sectors continued to be especially impacted by the global slowdown, while domestic demand rebounded on buoyant consumer confidence, stable retail prices and renewed investor confidence. Agriculture was a notably strong sector, with agricultural production increasing by 4.8 percent in 2008, the fastest growth since 1992. While agriculture now accounts for 14.4 percent of total output it continues to provide most or all of the support for 42 percent of households. Although Indonesia's direct exposure to troubled American and European-domiciled banks is limited, Indonesian bankers became more conservative in line with tightening global financial conditions. Far fewer new loans are being approved, and anecdotal reports suggest that some new customers have had difficulty accessing credit. While inter-bank lending has been improving and there is sufficient overall rupiah liquidity in the system, it is not evenly distributed with larger banks typically liquid and smaller banks facing problems. Nevertheless banking sector indicators continue to be relatively robust, and the nation's largest banks reported higher net profits in the first quarter of 2009.